Estudio de adaptabilidad y densidades de siembra del cultivo de chia (salvia hispanica), en la zona de Babahoyo”, provincia de los Ríos. - Santana Alvario, Samuel Eliseo (2013)
The research was established in the grounds of the farm "San Pablo" property of the Faculty of Agricultural Sciences, Technical University of Babahoyo, located at Km 7S via Babahoyo - Montalvo, Canton Babahoyo, and Province of Los Ríos. The aim was to evaluate the agronomic and crop seeding chia Babahoyo area. Treatments were for planting distances: 60, 50, 55, 45 and 40 cm. between rows. Experimental design was used "completely random blocks" with 5 treatments and 4 replications plant height was assessed at 60 days after planting, days to flowering, number of flowers per plant, fruit set, weight production 10 floors, number of plants per meter and yield per hectare. Comparison of treatment means were made with Turkey’s test at 95% probability.